Creative Thinking Skills of University Students - Boulassna, Farida; Ketfi, Yasmina (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
The current research aims to reveal the differences in creative thinking skills of university students in two different systems, a classical system and a LMD system, and to achieve this goal the comparative descriptive curriculum was relied upon, and the creative thinking test was relied upon as a data collection tool that was applied to a class sample of urban master's students (lysons lmd, holders of the Classic Engineering Certificate and returned to complete the master's degree). The results of the study showed that there were no statistically significant differences at the level of indication (0.05) in both intellectual fluency, automatic flexibility and creative originality in the sample of master's students 2 urbanization of a classical system and their counterparts in the LMD system despite the efforts of the Ministry of Higher Education to achieve many reforms, the most important of which is to encourage students to think creatively and the ability to produce knowledge in the university student.The study therefore suggested that the focus should be on developing appropriate teaching strategies to suit the new education system in order to demonstrate the effectiveness of the system, as well as the need to focus on the development of additional education programmes for the development of creative thinking among the university student. In addition to conducting studies on the effects of various education strategies, for example collaborative education strategies in developing the creative thinking skills of the university student in the new system. With the need to develop university education in accordance with quality standards (student quality, quality and integrity of the faculty, management quality, quality of material capabilities), and other international standards.